Case report: Severe combined immunodeficiency with ligase 1 deficiency and Omenn-like manifestation - Dabrowska-Leonik, Nel; Pastorczak, Agata Karolina; Bąbol-Pokora, Katarzyna; Bernat-Sitarz, Katarzyna; Piątosa, Barbara; Heropolitańska-Pliszka, Edyta; Kacprzak, Magdalena M.; Kalwak, Krzysztof; Gul, Katarzyna; Burg, Mirjam van der; Ussowicz, Marek; Pac, Malgorzata (Frontiers in Immunology, 2022)
DNA ligase I deficiency is an extremely rare primary immunodeficiency with only 6 patients reported in the literature. Most common manifestations include radiosensitivity, macrocytic anemia, lymphopenia with an increased percentage of gamma-delta T cells, and hypogammaglobulinemia requiring replacement therapy. Two-month-old girl with delayed development, T-B-NK+ SCID, and macrocytic anemia presented features of Omenn syndrome. Whole exome sequencing revealed two novel, heterozygous variants (c.2312 G>A , p.Arg771Gly and c.776+5G>T, p.Pro260*) in the LIG1 gene (NM_000234.1). Hematopoietic stem cell transplantation from a fully matched unrelated donor was performed at the age of 4 months using GEFA03 protocol. Mixed donor-recipient chimerism was observed, with 60-70% chimerism in the mononucleated cell compartment and over 90% in T-lymphocyte compartment, but autologous myeloid recovery. Stable CD4+ and CD8+ T-cell counts above 200/µL were achieved after 2 months, but the patient remained transfusion-dependent. Despite satisfactory immunological reconstitution, the second transplantation due to constitutional hemolytic defect has been considered. In light of possible re-transplantation, an issue of optimal conditioning protocol with sufficient myeloid engraftment is important. For the first time Omenn syndrome is described in a compound heterozygote carrying two the novel variants p.Arg771Gly and p.Pro260* in the LIG1 gene. Patients diagnosed with SCID and Omenn syndrome showing macrocytic anemia, should be screened for DNA ligase I deficiency.